PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI: Studi Kasus Pada Karyawan Grand Puri Saron Hotel Yogyakarta - Theofani Eirine Marlissa; I Made Hedy Wartana (Journal Research of Management, 2023)
Human resource management is an integral part of organizational management, specifically focusing on various aspects related to human resources. Organizational commitment refers to the degree to which an employee demonstrates a strong tendency to maintain a long-term relationship with the organization. Job satisfaction refers to the extent to which individuals express positive and negative feelings toward their occupation, including factors such as level of challenge and use of skills, as well as like the presence or absence of monotony in their work. Work environment includes the tangible, interpersonal, and psychological aspects of an organization that impact the performance and effectiveness of that organization's workforce. This study was conducted at the Grand Puri Saron Hotel Yogyakarta, a leading accommodation facility located in the Malioboro area of Sosrowijayan, Yogyakarta. The objective of this study is to determine the significant and dominant impact of the independent variable on the dependent variable. The study included 26 employees and used a saturation point sampling technique. The data analysis technique used in this study involved the use of multiple linear regression analysis, supported by IBM Statistic SPSS software. The results of this study indicate that there is no statistically significant relationship between the Work Environment variable and the Organizational Commitment variable. The variable Organizational Commitment is significantly and positively affected by Job Satisfaction, in which Job Satisfaction has the main effect